Tuberculosis in Germany: a declining trend coming to an end?. Issue 2 (22nd October 2015) - Fiebig, Lena; Hauer, Barbara; Brodhun, Bonita; Altmann, Doris; Haas, Walter
In the context of the newly adopted World Health Organization (WHO) End TB strategy, an action framework towards tuberculosis (TB) elimination in low incidence countries has been launched [1, 2]. Its aim is to reach pre-elimination of TB (less than 10 cases per one million inhabitants) by 2035 and TB elimination (less than one case per one million inhabitants) by 2050. Germany belongs to the addressed countries and territories with a TB incidence lower than 10 cases per 100 000 inhabitants. To reach these targets, Germany would have to have an annual reduction in the TB incidence of about 10% [1, 2]. Coinciding with the launch of the End TB Strategy, tuberculosis case numbers are re-increasing in Germany http://ow.ly/Tj2f0